Combination Of Platelet & Uric Acid Estimation Can Predict Severity Of Pih Better - DR ELLORA DEVI (International Journal of Pharma and Bio Sciences, 2012)
Individual predictive tests for Pregnancy Induced Hypertension (PIH) are yet to be reliable, valid, and economical. Therefore a combination of tests like platelet count & uric acid estimation was studied for assessing the severity of PIH. Platelet count and uric acid estimation are not only affordable but can be done even in rural setup. Present study focussed on platelet count and uric acid estimation together as indicator for severity of PIH. A total of 76 cases including 60 cases of PIH of varying severity were studied. Platelet count and serum Uric acid estimations were done throughout pregnancy. The mean platelet counts (Lacs/cmm): 244.12±11.44 control group, 182.93±19.37-mild PIH, 142.26±23.35-Moderate to severe PIH. The mean uric acid level (mg/dL): 3.88±0.51 in control group, 5.32±0.70- mild PIH, 6.85±0.97- Moderate to severe PIH. The platelet count fell while serum uric acid increased with increasing severity of PIH significantly (p < 0.05). Thus, it is concluded that platelet count and uric acid estimation together can be used as a good indicator of severity of PIH.